Differential ear growth of two maize varieties to shading in the field environment Effects on whole plant carbon allocation and sugar starvation response - Liang, Xiao-Gui (Journal of plant physiology, 2020)
Copyright © 2020 Elsevier GmbH. All rights reserved.